2019
DOI: 10.1097/qai.0000000000002123
|View full text |Cite
|
Sign up to set email alerts
|

Project Shikamana: Community Empowerment-Based Combination HIV Prevention Significantly Impacts HIV Incidence and Care Continuum Outcomes Among Female Sex Workers in Iringa, Tanzania

Abstract: Objective: To determine the impact of a community empowerment model of combination HIV prevention (Project Shikamana) among female sex workers (FSW) in Iringa, Tanzania. Methods: We conducted a 2-community randomized trial. Intervention elements included the following: (1) Community‐led drop‐in center and mobilization activities; (2) venue-based peer education, condom distribution, and HIV testing; (3) peer service navigation; (4) provider sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 23 publications
2
94
2
Order By: Relevance
“…In Cameroon, most community-based facilities serving FSWs currently offer services fairly focused on HIV prevention, testing, and treatment support, with family planning often limited to counseling. 69 Although these services appear to be an effective way to deliver HIV testing to FSWs, 70 they may miss opportunities for contraceptive provision. Requiring women to access multiple service points to meet their sexual and reproductive health needs may further disincentivize contraceptive use and act as a structural barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, most community-based facilities serving FSWs currently offer services fairly focused on HIV prevention, testing, and treatment support, with family planning often limited to counseling. 69 Although these services appear to be an effective way to deliver HIV testing to FSWs, 70 they may miss opportunities for contraceptive provision. Requiring women to access multiple service points to meet their sexual and reproductive health needs may further disincentivize contraceptive use and act as a structural barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, it has been demonstrated that FSWled mobilization for HIV services through community drop-in centers has been associated with reductions in HIV incidence among FSWs in Tanzania. 70 Expanding this community empowerment model for integrated family planning, STI, and HIV service delivery may represent an effective strategy to reduce unintended pregnancies and be responsive to critical health care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Sex workers need more specifically targeted services. Experience from a community-based study among FSWs in Tanzania that included community-led drop-in centre and mobilization activities as well as venue-based peer education, condom distribution, and HIV testing, showed significant reduction in HIV incidence [ 77 ]. Expanding such community-based model which reaches out to FSWs in their areas of work, to further include family planning services can be an effective strategy to reduce unintended pregnancy among FSWs.…”
Section: Discussionmentioning
confidence: 99%
“…Women trading sex have taken collective action to reduce their risks of violence, abuse, HIV/STIs, and to increase their access to healthcare and other income [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For example, they have mobilized for human rights via a group, meeting, or marches, sharing concerns and helping each other.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they have mobilized for human rights via a group, meeting, or marches, sharing concerns and helping each other. CM has reduced HIV/STI risk among women in the sex trade in India, the Caribbean, Brazil, and Africa [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Its dissemination in India has resulted in significant reductions in HIV prevalence at regional levels [ 22 ].…”
Section: Introductionmentioning
confidence: 99%